Chemical Profiling and Histamine Inhibitory Activity Assessment of Merremia Vitifolia and Bidens Pilosa Extracts - Candra Yulius Tahya; Karnelasatri Karnelasatri; Nelson Gaspersz (Molekul, 2023)
There are two species of plant that grow flourishing all around Indonesia including in Banten and West Java which are Merremia vitifolia and Bidens pilosa. In this study we evaluate how these plants could be potentially used as natural preserver of fish product especially Auxis thazard, to inhibit the histamine formation, and to find out how this activity correlates to the substances in polar extract of B. pilosa flowers and M. vitifolia leaves. Liquid chromatography with tandem mass spectrometry (LC-MS/MS) and gas chromatography-mass spectrometry (GC-MS) were used to identify the substances of the plant’s part extracts. There are 27 chemicals in M. vitifolia extract and 14 chemicals in B. pilosa extract that have been detected. A triglyceride has been detected, isolated, and characterized by FTIR, 1H-NMR and 13C-NMR from n-hexane extract of M. vitifolia supported by LC-MS/MS data. Histamine formation in fish was determined after 30 min treatment with 4-hydroxybenzoic acid solution is around 40 – 51 mg / 100 g of fish, while treatment with M. vitifolia and Bidens pilosa extracts were less than 10 mg / 100 g of fish. This is the indication of high potential of both extract as preserver of fish products. Many of the identified substances have bioactivity like antimicrobial, anticancer, anti-inflammatory, antioxidant, and more, which influence the extracts’ ability to inhibit the formation of histamine in fish.